Pengaruh Penggunaan Aplikasi Wattpad terhadap Kemampuan Menulis Cerita Pendek Siswa SMPN 1 Siak Hulu - Pristi Dian Nova; Rhani Febria (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
The lack of ability to write short stories in Indonesian Language and Literature subjects among students of SMPN 1 Siak Hulu is the main cause of this research. The purpose of this study was to see the effect of utilizing the Wattpad application on the ability to write short stories of SMPN 1 Siak Hulu students. This research was conducted in the odd semester of the 2024 school year. Held at SMPN 1 Siak Hulu, Jl. Kubang Jaya, Kec. Siak Hulu, Kampar Regency, Riau. This study used a pre-experimental design with the type of one group pretest-posttest. The research sample was 33 students selected by purposive sampling technique. Data collection was done with tests and documentation. The data analysis technique used to test the research hypothesis was t-test. Based on the results showed that the ability to write short stories before being given treatment using Wattpad obtained an average value of 67.61. Meanwhile, the results of research on the ability to write short stories using the Wattpad application showed an average score of 81.09. Based on the research objectives and data analysis, the significance level is 0.000 <0.05, with Thitung > Ttabel or 5.856 > 1.695. Thus, Ha is accepted, while H0 is rejected. Thus, it can be concluded that the utilization of the Wattpad application affects the ability to write short stories of SMPN 1 Siak Hulu students.